Peran Guru Sekolah Dasar dalam Menanamkan Nilai Disiplin dan Tanggung Jawab Pada Siswa Sekolah Dasar - Dewi Sulistianingsih; Nurul Agustina Ginting; Etalia Asso; Rifqa Gusmida Syahrun Barokah (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The cultivation of discipline and responsibility is an essential aspect of character development among elementary school students. These values contribute to the formation of positive behaviors that support academic achievement and social life. Teachers play a strategic role in fostering character values through learning activities and daily habituation practices at school. This study aims to describe the role of teachers in instilling discipline and responsibility among students at SDN 020 Tambusai Utara. The research employed a qualitative approach, with data collected through interviews with four teachers. The findings revealed that teachers promote discipline and responsibility through role modeling, habituation, the implementation of school and classroom rules, and positive reinforcement. Responsibility is developed through learning assignments, classroom duty schedules, maintaining school cleanliness, and carrying out simple classroom responsibilities. The study also identified several challenges faced by teachers, including differences in students’ characteristics, limited parental support, peer influence, and excessive use of digital devices. To address these challenges, teachers apply personal approaches, provide continuous guidance, and strengthen collaboration with parents. The findings indicate that the successful development of discipline and responsibility requires synergy among schools, families, and the wider community to support students’ positive character growth.